2020
DOI: 10.1007/s13197-020-04879-4
|View full text |Cite
|
Sign up to set email alerts
|

Application of E-nose technique to predict sugarcane syrup quality based on purity and refined sugar percentage

Abstract: Rapid test methods with portable devices along with standard chemical tests are necessary to determine raw syrup quality in the sugarcane agro-industries. On this account, a special e-nose device was developed to test the sugarcane syrup and its association with the odor emitted from it to determine the amount of sucrose (purity) in the sugarcane syrup. Samples were obtained from the farms of Hakim-Farabi agro-industry, including four varieties (CP57, CP69, IRC99-02, and CP48). Experiments included chemical te… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3
1
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 24 publications
0
3
0
Order By: Relevance
“…With these models, they were able to estimate the drying time of mint leaves with 93% accuracy. Zaki Dizaji, et al [ 32 ] used the electronic nose technique and the PLS, PCR, and MLR models to predict the quality of sugarcane syrup based on the purity and the percentage of refined sugar. They stated that the accuracy of the PLS method for this purpose was 77 and 71%, respectively; they also reported that the accuracy of the PCR method was 72% and 68%, respectively.…”
Section: Discussionmentioning
confidence: 99%
“…With these models, they were able to estimate the drying time of mint leaves with 93% accuracy. Zaki Dizaji, et al [ 32 ] used the electronic nose technique and the PLS, PCR, and MLR models to predict the quality of sugarcane syrup based on the purity and the percentage of refined sugar. They stated that the accuracy of the PLS method for this purpose was 77 and 71%, respectively; they also reported that the accuracy of the PCR method was 72% and 68%, respectively.…”
Section: Discussionmentioning
confidence: 99%
“…The difference in responses of consumers may present differentiated preference patterns [26]. While, in classic consumer science, liking is measured with the 9-point hedonic scale [27,28], principal component analysis (PCA) is widely used as a multivariate analytical, statistical technique that can be applied to quantitative descriptive analysis for sensory evaluation of various food and dairy products [29][30][31][32][33][34][35][36].…”
Section: Introductionmentioning
confidence: 99%
“…and effective method, allowing for immediate monitoring and analysis. Nevertheless, in order to fully exploit the capabilities of e-nose technology, it is crucial to have uninterrupted connectivity and reliable data transmission [4], [5]…”
mentioning
confidence: 99%